Analisis Faktor Pembentuk Dalam Melakukan Keputusan Mendaftar di SMA Islam Al Azhar 14 Semarang - Istivani, Yulia; Luqman, Yanuar; Setyabudi, Djoko (Interaksi Online, 2024)
Private schools cannot be separated from the commercial activities within them to achieve the school's target enrollment. Al Azhar 14 Islamic High School is a relatively new Islamic private school in the city of Semarang. However, Al Azhar 14 Islamic High School can show quite rapid and significant development in terms of the number of applicants or students from the first generation to the present. For this reason, this research was carried out to find out what factors can influence applicants or students to make the decision to register at this school so that the school can review and also consider these factors for the benefit of the school. This research is quantitative research with an exploratory type using factor analysis techniques. Researchers collected various basic concepts regarding factors that influence decision making to register and collected 18 factors which will be analyzed further. The respondents of this research were 100 students at SMA Islam Al Azhar 14 Semarang and then the data obtained was processed using IBM SPSS through several stages of factor analysis data processing. Of these 18 factors, five new factors were produced, namely School Facilities Factors, SpiritualIntellectual Education Factors, Organizational Strategy Factors, Non-Academic Factors, and Security Reputation Factors. However, the results of data processing also show that the School Facilities Factor (component 1) is the most appropriate factor to summarize the 18 existing factors.